Ese music: honours for the dead: status for the sponsor - Nzewi, Meki (International Library of African Music, 1987)
The Igbo society is a distinct culture area in the political entity called Nigeria. Nigeria, population estimated at over 88 millions, is a country populated by over 248 distinct linguistic-cultural groups. A fast modernising nation naturally endowed with mineral (predominantly oil) wealth, and now practising a presidential system of modern government (since October 1979) after 13 years of military rule, Nigeria is a nation where modern technology and value systems operate in apposition with traditional belief systems.
Keywords: African Music